PMO-236 Are guidelines followed in histology reporting in inflammatory bowel disease (IBD)?. (28th May 2012) - Daker, C; Haji-Coll, M; Besherdas, K
Abstract : Introduction: IBD has 240 000 suffers in the UK. Diagnosis is made on consideration of clinical, macroscopic, microscopic and radiological findings to classify Crohns disease (CD), ulcerative colitis (UC) and IBD type unclassified (IBDTU) (previously indetermediate colitis). An accurate diagnosis to differentiate between the different types of IBD is important as evidence based treatment differs among the different types. An accurate histological classification of IBD increases diagnostic accuracy by 5%–41%. In line with the BSG 2011 IBD guidelines, histopathology should "attempt to define the type of IBD, mention other coexistent diagnoses, or complications and the absence or presence of any dysplasia and its grade". There are eight recognised histological features consistent with a UC diagnosis and two further criteria to differentiate between active, inactive or quiescent disease. That for CD includes nine features with a further three to mark active disease. Methods: To assess whether histopathology reporting in IBD are in line with BSG guidelines. Using the BSG guideline "A Structured Approach to Colorectal Biopsy" the histopathology reports of 60 IBD patients were scrutinised to see if they correlated with the guideline; examined for 8 histological features of UC, 9 for CD, disease activity, complications and presence and grade of dysplasia. Results: The cohort identified 60 patients (38 UC, 22 CD). The type of IBD was specified in 25% (IBDTU 3%, UC 10%, CD 4%) and not mentioned in 40%. 23% of UC specimens were labelled as such by the histolpathologist; in that cohort there was also 3% IBDTU, 37% "IBD", 0% CD. In the CD group; 0% IBDTU, 4% UC, 18% CD, 28% "IBD". 80% of specimens had no mention of complications/coexistent features. Of those documented CMV was noted in only 1 UC case, fistulae in 2 CD cases and infection in a total of nine across the groups. Dysplasia was not mentioned in 22% UC and 59% CD; listed as a relevent negative finding in 71% UC and 36% CD and identified as low grade dysplasia (tubuloadenoma) in 3 UC cases and 1 CD case. The features most frequently identified: In UC: (1) severe crypt architectural distortion; (2) severe widespread decreased crypt density, In CD it was (1) mucosal surface normal, irregular, villous; (2) crypt atrophy. Conclusion: In our study the majority of histology reports lack important information pertaining to and even attempting to classify IBD. On average for patients suffering from CD or UC, the histological reports only state two histological signs which are of immense importance in confirming either diagnosis. None of the histological reports mentioned all the signs in UC or CD either as positives or relevant negatives. The importance of good histological reporting may help clinicians in differentiating between the different IBD types which in turn may help guide optimum evidence based management. Competing interests: None declared.